РАЗРАБОТКА КОНЦЕПЦИИ ДВУХФАЗНОЙ СИСТЕМЫ ТЕПЛООТВОДА СПУТНИКА - Турна, Рустем Юсуфович (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2021)
For spacecraft (SC) with power unit capacity more than 4 ... 6 kW promising construction of thermal control system (TCS) based on two-phase mechanically pumped loops (2PMPL). The development of 2PMPL has been carried out quite intensively since the early '80s. However, so far there are no examples of practical implementation of such high-power systems. One of the main reasons mentioned is the novelty of the system, and insufficient study of its operation in space conditions, which adds risks. The most important component of such systems is a heat rejection subsystem (HRS), whose task is to reject heat from the coolant and radiate it into space. In its turn, HRS is also a system, the design of which requires using a system approach, considering various aspects of its operation. HRS includes a heat-hydraulic network and a radiation heat exchanger (RHE). The key elements of the HRS are condensers (CC), quite new devices for space technology. This paper presents an algorithm for the design and optimization of the heat rejection subsystem (HRS) of a satellite two-phase thermal control system. The methodology of engineering synthesis of complex technical systems and informal procedures for multi-criteria optimization of elements and subsystems at various stages of HRS design is repeatedly used. t is shown that optimization should be carried out both at the level of elements and subsystems, and at the level of the whole thermal control system. As a result of the study, the HRS design is proposed, which uses condensers in the form of smooth steel tubes of constant cross-section and their series-parallel connection scheme in the hydraulic network. Main advantages of the design: traditional for single-phase loops elements are used; operation of elements and subsystems in zero gravity conditions is predictable and allows complete testing on the ground without mandatory flight experiment; the system is operable at high saturation pressures (temperatures) (on ammonia - up to 85℃).